Improving Students' Scientific Literacy and Cognitive Learning Outcomes through Ethnoscience-Based PjBL Model - Rusmansyah Rusmansyah; Leny Leny; Hana Nabilla Sofia (Journal of Innovation in Educational and Cultural Research, 2023)
Scientific literacy is one of the basic skills to compete in an increasingly competitive life. Nevertheless, Indonesian students continue to have low levels of scientific literacy. This study aims to determine the difference in students' scientific literacy and cognitive learning outcomes in the experimental and control classes and to find students' responses to the ethnoscience-based PjBL model in learning. This quasi-experimental research applies a non-equivalent control group design. The samples were eleventh-grade science students at SMA Negeri 2 Banjarmasin in the even semester of the 2021/2022 academic year. The data were collected using test and non-test methods. The instruments were scientific literacy and cognitive learning tests and a response questionnaire as a non-test instrument. The data were analyzed using descriptive and inferential analysis. The results showed significant differences in scientific literacy and cognitive learning outcomes between students in the experimental and control classes. The ethnoscience-based PjBL model gets a very good response. This study concludes that implementing the ethnoscience-based PjBL model can improve students' scientific literacy and cognitive learning outcomes. This study contributes to chemistry learning by improving scientific literacy and learning outcomes through the ethnoscience-based PjBL model.